Unveiling the Role of Risk-Taking Ability in Mediating the Influence of Entrepreneurship Education, Digital Financial Literacy, and Financial Self-Efficacy on Students’ Courage to Start a Business - Sutrisno; Garin Pratiwi Solihati; Syamsuri; Susatyo Adhi Pramono; Imam Jayanto; Muhammad Aqib Shafiq (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze the effects of Entrepreneurship Education, Digital Financial Literacy, and Financial Self-Efficacy on Students’ Courage to Start a Business, with Risk-Taking Ability as a mediating variable. A quantitative approach with a survey design was employed, with 100 university students in Banyumas Regency selected via purposive sampling. Data were collected through a structured online questionnaire and analyzed using SEM-PLS with a bootstrapping procedure. The results indicate that Entrepreneurship Education, Digital Financial Literacy, and Financial Self-Efficacy have positive and significant effects on Risk-Taking Ability. Furthermore, Risk-Taking Ability has a positive and significant effect on Students’ Courage to Start a Business. In addition, Risk-Taking Ability is proven to positively and significantly mediate the effects of the three independent variables on students’ entrepreneurial courage. These findings suggest that students’ entrepreneurial courage is largely determined by their ability to assess risks and opportunities and to make decisions under uncertainty. This study contributes theoretically by uniquely integrating financial aspects and psychological aspects within a single framework grounded in the Theory of Planned Behavior, Social Cognitive Theory, and Behavioral Finance Theory. By linking students’ digital financial capability with their risk-taking ability, the model explains how financial knowledge strengthens psychological readiness in entrepreneurial decision-making. The findings also provide practical implications for higher education institutions and policymakers in designing entrepreneurship programs that simultaneously develop digital financial competence and risk-taking capacity.